Upaya domestikasi ikan Tambakan (Helostoma temminckii) yang tertangkap dari sungai Sebangau - Tania Serezova Augusta (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This study aims to determine the level of adaptability of Tambakan (Helostoma temminckii) were caught from Sebangau river through the process of domestication, and to know the stages in the domestication process. Study was done from April to July 2016. The research method used was observation. For domestification, 500 fishes were reared in plactic tank with the size of 3x2x1 m, and 75 cm of water depth. Feed were given as much as 3% of the fish weight/day, and feeding was done twice a day (morning and afternoon). Survival rate (SR) of fishes during the rearing period amounted to 81%. Feed Conversion Ratio obtained was 3.3. The average weight gains of fishes were 3-4 g / fish every two weekly sampling. The condition of water quality of domestification tank were dissolved oxygen (DO) 3.6 mg/L, pH 7.2 and temperature 29 0C. Key words : Domestication, Helostoma temminckii, water quality.